Electronic Principles of Hydrogen Incorporation and Dynamics in Metal Hydrides - Ljiljana Matović (Crystals, 2012)
An approach to various metal hydrides based on electronic principles is presented. The effective medium theory (EMT) is used to illustrate fundamental aspects of metal-hydrogen interaction and clarify the most important processes taking place during the interaction. The elaboration is extended using the numerous existing results of experiment and calculations, as well as using some new material. In particular, the absorption/desorption of H in the Mg/MgH2 system is analyzed in detail, and all relevant initial structures and processes explained. Reasons for the high stability and slow sorption in this system are noted, and possible solutions proposed. The role of the transition-metal impurities in MgH2 is briefly discussed, and some interesting phenomena, observed in complex intermetallic compounds, are mentioned. The principle mechanism governing the Li-amide/imide transformation is also discussed. Latterly, some perspectives for the metal-hydrides investigation from the electronic point of view are elucidated.